Detrital zircon geochronology of Cordilleran retroarc foreland basin strata, western North America. Issue 5 (17th September 2013) - Laskowski, Andrew K.; DeCelles, Peter G.; Gehrels, George E.
Abstract [1] We present a compilation of 8717 U‐Pb analyses from 95 detrital zircon samples of Jurassic‐Eocene North American Cordillera foreland basin strata. Of these samples, 30 are new and previously unpublished. Variation in detrital zircon age spectra between samples records erosion or recycling of basement and cover rocks within the Cordilleran orogenic wedge. Each sample can be classified into one of six major provenance groups, whose age spectra suggest derivation from (1) Mesozoic eolianites of the western United States, (2) Paleozoic passive margin strata of the western United States, (3) Paleozoic passive margin strata of western Canada, (4) the Mogollon Highlands, (5) the Cordilleran magmatic arc, or (6) Yavapai‐Mazatzal Province crystalline basement rocks. Referencing these provenance interpretations to their location and stratigraphic deposition age produces a detailed spatial and temporal record of sediment dispersal within the foreland basin system. Late Jurassic provenance is dominated by recycling of Mesozoic eolianites from sources in the Sevier thrust belt. Cretaceous‐Eocene provenance is dominated by recycling of the passive margin, with increasing complexity upsection. We interpret that this provenance transition records a basin‐wide unroofing sequence. A composite age‐probability plot of 1539 young (<250 Ma) detrital zircons reveals at least four age‐abundance peaks that we interpret to represent periodic high‐flux magmatism in the Cordilleran arc.